A Comparison Study on Functions for Lane Change Path in Emergency Obstacle Avoidance - A.S.P. Singh; A. Putra; K.A. Abu Kassim (Journal of the Society of Automotive Engineers Malaysia, 2022)
In situations in which autonomous emergency braking is ineffective in avoiding an obstacle encountered in the current lane, autonomous emergency steering may be useful in avoiding the obstacle. This paper focuses on the comparison of the lane change paths by using autonomous emergency steering. Six functions that are considered for the generation of the desired lane change path are circular arcs, ramp sinusoidal, polynomial, clothoid, trapezoidal acceleration profile, and sigmoid. The longitudinal distance required to avoid the obstacle which is the total longitudinal distance for the complete lane change is calculated for different vehicle speeds and tire-road friction coefficients. The distances obtained for the six functions are compared and the function that achieves the shortest longitudinal distance to avoid the obstacle is regarded as the most effective function. For a total lateral displacement of 3.5 m and friction coefficients of 0.9, 0.5, and 0.2, circular arcs give the shortest and clothoid gives the longest longitudinal distance required to avoid the obstacle.